PIK3CA mutation enrichment and quantitation from blood and tissue - Keraite, Ieva; Alvarez-Garcia, Virginia; Garcia-Murillas, Isaac; Beaney, Matthew; Turner, Nicholas C.; Bartos, Clare; Oikonomidou, Olga; Kersaudy-Kerhoas, Maïwenn; Leslie, Nicholas R. (Scientific reports, 2020)
PIK3CA is one of the two most frequently mutated genes in breast cancers, occurring in 30–40% of cases. Four frequent ‘hotspot’ PIK3CA mutations (E542K, E545K, H1047R and H1047L) account for 80–90% of all PIK3CA mutations in human malignancies and represent predictive biomarkers. Here we describe a PIK3CA mutation specific nuclease-based enrichment assay, which combined with a low-cost real-time qPCR detection method, enhances assay detection sensitivity from 5% for E542K and 10% for E545K to 0.6%, and from 5% for H1047R to 0.3%. Moreover, we present a novel flexible prediction method to calculate initial mutant allele frequency in tissue biopsy and blood samples with low mutant fraction. These advancements demonstrated a quick, accurate and simple detection and quantitation of PIK3CA mutations in two breast cancer cohorts (first cohort n = 22, second cohort n = 25). Hence this simple, versatile and informative workflow could be applicable for routine diagnostic testing where quantitative results are essential, e.g. disease monitoring subject to validation in a substantial future study.